2010
DOI: 10.1136/gut.2009.196626
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight heat shock protein HSP27 is a prognostic indicator in rectal cancer but not colon cancer

Abstract: In a large cohort of patients with a poor prognosis, HSP27 is an independent marker of poor outcome in rectal cancer; its expression is not altered by neoadjuvant radiotherapy. This finding requires validation in an independent similar cohort of patients with rectal cancer. HSP27 levels merit evaluation as a stratification factor for treatment of rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 53 publications
1
48
1
Order By: Relevance
“…Our results differed from previous studies in NSCLC [18]. We found that the expression of HSP27 was significantly higher in lung adenocarcinoma tissues, which was consistent with the results in most of the literature [12][13][14][15][16][17]. However, we also found that HSP27 expression did not significantly correlate with the clinicopathological features of lung adenocarcinoma patients.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Our results differed from previous studies in NSCLC [18]. We found that the expression of HSP27 was significantly higher in lung adenocarcinoma tissues, which was consistent with the results in most of the literature [12][13][14][15][16][17]. However, we also found that HSP27 expression did not significantly correlate with the clinicopathological features of lung adenocarcinoma patients.…”
Section: Discussioncontrasting
confidence: 66%
“…HSP27 is overexpressed in many tumors and has a certain correlation with prognosis. Studies have shown that overexpression of HSP27 is associated with poor prognosis of some malignant tumors, such as liver [14], prostate [15], and colon [16] cancers. In contrast, cervical cancer [12] and oral squamous cell carcinoma [13] patients have better prognosis when HSP27 is overexpressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of that outcome may be closely related to tissue-specific expression. HSP27 has been reported to be overexpressed and associated with poor prognosis in many human cancers, including breast, rectal, gastric, lung, liver and prostate cancers (33)(34)(35)(36). Contrary to the findings in most cancers, in human esophageal squamous cell carcinoma (HESCC), the expression of HSP27 was low, and this low expression was correlated with poor prognosis (37,38).…”
Section: Discussionmentioning
confidence: 96%
“…At the end of CRS, i.e., at the beginning of HIPEC, Hsp27 levels significantly increased in patients with PC, but not in those with cancer or a history of cancer who underwent abdominal surgery. Hsp27 expression has been described as an independent prognostic factor for patients with ovarian carcinomas, constituting 36 % of those in groups 1, and in patients with rectal cancer (Geisler et al 2000;Tweedle et al 2010). Moreover, in patients without cancer with inflammatory disease, abdominal surgery did not increase Hsp27 levels.…”
Section: Discussionmentioning
confidence: 89%